2017
DOI: 10.3847/1538-4357/aa9077
|View full text |Cite
|
Sign up to set email alerts
|

Accretion Flow Properties of Swift J1753.5-0127 during Its 2005 Outburst

Abstract: Galactic X-ray binary black hole candidate Swift J1753.5-0127 was discovered on June 30 2005 by Swift/BAT instrument. In this paper, we make detailed analysis of spectral and timing properties of its 2005 outburst using RXTE/PCA archival data. We study evolution of spectral properties of the source from spectral analysis with the additive table model fits file of the Chakrabarti-Titarchuk two-components advective flow (TCAF) solution. From spectral fit, we extract physical flow parameters, such as, Keplerian d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…According to Bharali et al (2019), the orbital period of the source is 14.7 hrs. So, this nature of the non-observation of the softer spectral states is consistent with other short orbital period objects, such as MAXI J1836-194 (Jana et al 2016), Swift J1753.5-0127 (Debnath et al 2017), XTE J1118+480 . A similar presence of only HS during 2000 & 2005 outbursts of the short orbital period (∼ 4.1 hrs) transient BHC XTE J1118+480 was noticed (see, Debnath et al 2020).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…According to Bharali et al (2019), the orbital period of the source is 14.7 hrs. So, this nature of the non-observation of the softer spectral states is consistent with other short orbital period objects, such as MAXI J1836-194 (Jana et al 2016), Swift J1753.5-0127 (Debnath et al 2017), XTE J1118+480 . A similar presence of only HS during 2000 & 2005 outbursts of the short orbital period (∼ 4.1 hrs) transient BHC XTE J1118+480 was noticed (see, Debnath et al 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Depending upon the nature of outbursts, transient black hole candidates (BHCs) show two types of outburst, such as type-I and type-II (Debnath et al 2017). Those outbursts, where all four canonical spectral states are observed in the above mentioned sequence, are known as type-I or classical outburst.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two and half decades of the post RXTE era, GX 339-4 showed outbursts of both type-I & II. According to Debnath et al (2017), in type-I or complete outbursts, all four commonly identified spectral states (HS, HIMS, SIMS, SS) are found to form hysteresis loop, while in the type-II or harder spectral states, we do not see any soft spectral state. Sometimes even intermediate states are found to be missing in the type-II outbursts.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 81%
“…m h , X s , R) other than mass of the black hole (M BH ) and normalization (N). In the recent years, accretion flow dynamics around several black holes are studied quite successfully using TCAF model [45][46][47][48]. Frequencies of the dominating QPOs are predicted from the TCAF model fitted shock parameters [49].…”
Section: Hsmentioning
confidence: 99%